The experience of laser light feedback in back-squat resistance training - Stien, N.; Andersen, V.; Solstad, T. E. J.; Saeterbakken, A. H.; Engelsrud, G. H. (Frontiers in Sports and Active Living, 2023)
The purpose of this paper is to contribute to the existing literature on performance in resistance-training (RT) by addressing how a phenomenological perspective on experiences with inter-kinaesthetic affectivity can illuminate experience of practicing RT with non-verbal, visual feedback provided through laser lights attached to the barbell. The material is created from qualitative interviews and using inter-kinaesthetic affectivity as analytical lenses. The findings show how participants interpret the feedback in the moment and explain how they adjust their movement in dialogue with the feedback and enable the “uptake” of feedback in their embodied experience. The findings show how the participants developed an awareness of how they can equalize the balance on their feet. We discuss what this means for the understanding of the training process in terms of how practitioners can use the uptake of non-verbal, visual feedback to immediately adjust the quality of their performance by responding kinaesthetically and bodily. The discussion contributes to the question of what kind of role a practitioner’s own kinaesthetic and bodily experiences have in the development and organization of RT. Perspectives that include the lived and intersubjective body as a knowledge position are promising for illuminating the whole bodied engagement that is necessary to understand how to perform RT.